Perempuan dan Politik Kekerabatan pada Pilkada Tahun 2020 di Jawa Tengah - Arif Sofianto (Bestuurskunde: Journal of Governmental Studies, 2021)
One of the entrances for women in politics is through kinship. In the 2020 regional head elections in Central Java, the nomination of women from incumbent families or political elites took place in various regions. Some have political experience; some have less experience. This paper examines how the nomination and victory of female candidates, whether because of kinship, or the need for experience, personal qualities, or other reasons. This research is descriptive with a qualitative approach, using data from the results of the vote, candidate data, and some related information. This study found that female candidates with kinship relations do not always win elections, but must have political capital, social capital, and competence, as well as support from political parties.